Proceedings of the 8th International Conference on Learning Analytics and Knowledge 2018
DOI: 10.1145/3170358.3170390
|View full text |Cite
|
Sign up to set email alerts
|

Analytics-enabled teaching as design

Abstract: As a human-centred educational practice and field of research, learning analytics must account for key stakeholders in teaching and learning. The focus of this paper is on the role of institutions to support teachers to incorporate learning analytics into their practice by understanding the confluence of internal and external factors that influence what they do. In this paper, we reconceptualise 'teaching as design' for 'analytics-enabled teaching as design' to shape this discussion to allow for the considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…As Alhadad, Thompson, Knight, Lewis, and Lodge (2018) argue, LA needs to move its focus away from "end-state outcomes" (p. 429) toward designs for student learning and teaching practice. However, education systems are continuously evaluated in terms of student outcome and value of investment, where student achievement needs to be measurable in some way.…”
Section: The Current Researchmentioning
confidence: 99%
“…As Alhadad, Thompson, Knight, Lewis, and Lodge (2018) argue, LA needs to move its focus away from "end-state outcomes" (p. 429) toward designs for student learning and teaching practice. However, education systems are continuously evaluated in terms of student outcome and value of investment, where student achievement needs to be measurable in some way.…”
Section: The Current Researchmentioning
confidence: 99%
“…Although data literacy is an increasing focus of education research, LA raises new potential for the use of data in practice, yet little is understood in terms of how pre-service teachers at the start of their professional learning conceptualise data and its use in possible use in practice (Earl & Timperley, 2009). LA, as an enabling technology, requires the integration of skills in the areas of data literacy, learning design and the effective use of learning technologies (Alhadad et al, 2018;Thompson et al, 2018). To date, there is limited research on teachers' use of LA in schools (see, for example, the call for a special issue of the Journal for Learning Analytics; Society for Learning Analytics Research, 2020), and this work has not focused specifically on the data literacy of pre-service teachers.…”
Section: La and Learning Designmentioning
confidence: 99%
“…Data literacy is essential for instructor interpretation and use of LA data. However, significant evidence suggests educators across all levels may not possess sufficient data literacy competencies (Alhadad et al, 2018;Hoogland et al, 2016;Ndukwe & Daniel, 2020;Tsai & Gašević, 2017). This is critical because difficulty analyzing and interpreting educational data hinders effective teacher inquiry (Sergis & Sampson, 2017).…”
Section: Data Literacymentioning
confidence: 99%
“…Farrell et al (2017) found the value university instructors placed on different types of LA related to their epistemic beliefs. Hence, researchers have observed that instructors practice epistemic fluency and data literacy when interpreting LA data and connecting it to their LD (Alhadad et al, 2018;Alhadad & Thompson, 2017).…”
Section: Pedagogical Lensmentioning
confidence: 99%
See 1 more Smart Citation